Fixed versus variable rest period effects on herbage accumulation and canopy structure of grazed 'Tifton 85' and 'Jiggs' Bermuda grass - Pedreira, Carlos Guilherme Silveira; Silva, Valdson José da; Guimarães, Murilo Saraiva; Pequeno, Diego Noleto Luz; Tonato, Felipe (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effects of variable and fixed rest periods on the forage production, plant-part composition, and canopy structural characteristics of 'Tifton 85' and 'Jiggs' Bermuda grass (Cynodon spp.) pastures under rotational stocking. The treatments were two grass cultivars (Jiggs and Tifton 85) and two rest periods (grazing starting whenever the canopy reached 25 cm or every 28 days, regardless of canopy height). A completely randomized experimental design, with a 2×2 factorial arrangement (two grass cultivars and two managements), was used with three replicates. The experiment was carried out during the summer growing season in Piracicaba, SP, Brazil. Pre- and post-grazing forage mass chacteristics were evaluated. 'Jiggs' and 'Tifton 85' canopies had similar light interception (96.8%) at pre-grazing, for fixed and variable rest periods; however, they showed different canopy structural characteristics. 'Jiggs' had greater stem proportion, greater canopy height during pre-grazing, and lower leaf area index. There were no differences between strategies and between grass cultivars for total yield, which averaged 16.8 Mg DM ha-1. Fixed and variable rest periods can be used for 'Tifton 85' and 'Jiggs' Bermuda grass.
Keywords: Cynodon; canopy height; grazing frequency; light interception; pasture management; regrowth